Conductance characteristics of current-carrying d-wave weak links - Shevchenko, S.N. (Физика низких температур, 2009)
The local quasiparticle density of states in the current-carrying d-wave superconducting structures was studied theoretically. The density of states can be accessed through the conductance of the scanning tunnelling microscope. Two particular situations were considered: the current state of the homogeneous film and the weak link between two current-carrying d-wave superconductors.